Pengaruh Tantangan Distribusi Terhadap Strategi Pemasaran Pada UMKM Tradisional Pasca Bencana - Muhammad Rafi; Umar Iskandar; Yusrawati Yusrawati; Al Mahfud Saputra (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Written This study examines the impact of distribution challenges on marketing strategies among traditional stone mortar (cobek) SMEs in Bireuen Regency in the aftermath of flooding. A quantitative approach was employed using a survey method, with data collected from 40 respondents through a saturated sampling technique. The data were analyzed using simple linear regression with SPSS. The findings reveal that distribution challenges exert a positive and statistically significant effect on marketing strategies, with a regression coefficient of 1.141 and a significance level of 0.000 (p < 0.05). The coefficient of determination (R²) of 0.752 indicates that 75.2% of the variance in marketing strategies is explained by distribution-related constraints. These results suggest that disruptions in distribution primarily caused by damaged infrastructure and limited transportation access following the disaster do not merely hinder business operations but actively drive SMEs to adopt more adaptive marketing strategies. In response, business actors increasingly rely on digital platforms, expand market reach, and implement more flexible selling approaches.